Hepatitis C Prevalence on the Rise but Screening at Safety Net Institutions Lagging behind - Jarin Prasa; Syed S. Karim; Bobby Jacob; Paul Mustacchia (International Journal of Hepatology)
Introduction. In the United States, the hepatitis C virus (HCV) is a leading contributor to liver-related illnesses and fatalities. Despite effective antiviral medications, acute infections have increased in recent years, likely due to IV drug use and the opioid epidemic. Previous guidelines recommended one-time screening for individuals born between 1945 and 1965. The CDC now recommends screening all adults over 18 unless there is a low prevalence in the area. Accurate measurement of HCV prevalence is essential for targeted prevention. In New York, over 100,000 individuals have HCV. We present data on HCV screening at a safety net hospital in Long Island, NY. Objective. To identify screening rates for hepatitis C and the exposure prevalence and specific demographics of a community in Long Island, NY. Methods. We performed a review of all patients seen in our hospital from 2012 to 2019. We identified patients born in the years 1945 to 1965 using our electronic medical record (EMR) system and subsequently analyzed those who were anti-HCV positive. We reviewed their demographics, including age, gender, and ethnicity, as well as their history of intravenous drug use and HIV coinfection status. Basic statistical analysis was used. Results. Our study identified 21,722 patients born between 1945 and 1965 and found that only 8.5% or 1,858 individuals were screened for hepatitis C. Among them, we found that 5.9% (109) tested positive for HCV antibody, with 3.0% (56) having an active infection. Demographic characteristics of those with HCV antibodies included 70.6% male, 53.2% Caucasian, 33.9% Black, and 15.6% persons who inject drugs (PWID). Conclusion. Our study findings suggest that a significant portion of patients in our community had missed opportunities for screening in our hospital. Our community had an estimated 5.9% prevalence, higher than the national and state averages. Caucasian men had higher prevalences. This study suggests the need for broader screening initiatives and more focused resource allocation, perhaps to safety net institutions, to decrease the burden of HCV.